PENGARUH KEPEMIMPINAN, MOTIVASI, DAN PELATIHAN TERHADAP KINERJA KARYAWAN, STUDI PADA PT SURYA TOTO INDONESIA TBK. PLANT CIKUPA TANGERANG - ., Masruri (EKONOMI BISNIS, 2018)
Employee performance can be traced back to the behavior of people in their working place in accordance with their role in the company. Performance assessment is carried out to provide information as a basis for decision making in an effort to improve the quality of company services. There are many factors that influence employee performance including leadership, work environment, work placement, career development, training, education, attendance, work culture and others. The study sought to establish the effect of leadership, motivation and training on employee performance in PT Surya Toto Indonesia Tbk both individually and jointly. A survey method was applied using primary data obtained from the questionnaire. Population in this study was employees of PT. Surya Toto Indonesia Tbk plant Cikupa Tangerang. Sample size was 100 employees, consisted of permanent employee and contracted employee, using Stratified Random Sampling technique. Data quality was verified using validity test and reliability test. Data were analyzed using multiple linear regression, T-test, F-test, coefficient of determination, and classical assumption test.The result of multiple linear regression analysis showed that leadership, motivation and training have positive influence to employee performance in PT Surya Toto Indonesia Tbk. This is indicated by positive regression coefficient numbers. It was also found that leadership, motivation and training have a significant effect to employee performance in PT Surya Toto Indonesia Tbk. indicated by the significance number generated in each variable below 0.05 from T-test and F-test. Based on the result of the coefficient of determination, the influence of leadership, motivation, and training variables on employee performance was 44.9% while the rest (100% - 44.9% = 54.1%) was explained by other variables that were not used in this study.